Ordinances Ordained and Established by the Mayor & City Council of the City of New Orleans 66 (1817) - (:unkn) unknown (My University, 1817)
Art. 10. It shall not be lawful for any person to have or keep within the city and suburbs, or within two miles of the same (except the public magazine, or place of depot appointed for that purpose) any quantity of gunpowder, at any one time, exceeding one hundred pounds weight, in any one place, house, store or out-house, which said quantity of one hundred pounds shall be separated in several stone jugs or tin canisters, each of which shall not contain more than ten pounds of powder, and shall be provided with a safe and sufficient stopple; and if any person or person shall keep any greater quantity of gunpowder at any one time than one hundred pounds, in any one place, house, store or out-house, or if the same gunpowder, so kept as aforesaid, shall not be separated in the manner herein above directed, he, she, or they shall forfeit all such gunpowder so kept contrary to the true intent and meaning of this ordinance, or so permitted to be kept, and which shall not be separated as aforesaid, and shall also forfeit and pay a fine not less than twenty-five, nor more than one hundred dollars, to be recovered with costs of suit, by the Mayor or any other competent magistrate; one half to the informer, and the other half for the use of the city
Keywords: GUNPOWDER - STORAGE